Lymphocytic Mastitis preceding Sjögren’s Syndrome - Ríos, Grissel; Peredo, Rubén A. (Puerto Rico Health Sciences Journal, 2010)
Sjögren’s syndrome (SS) is a chronic autoimmune disease characterized by lymphocytic infiltration of exocrine glands and B cell hyperreactivity. Lacrimal and salivary glands are the most commonly involved causing keratoconjunctivitis sicca and xerostomia. A wide variety of other glandular and extraglandular manifestations can occur in SS. Lymphocytic mastitis is a rare presentation of several conditions including diabetes mellitus and autoimmune disorders. We report a case of a 43 year-old woman with a four-year history of arthralgias and positive antinuclear antibodies who developed a right painless breast mass. Biopsy revealed lymphocytic mastitis with predominant B cells. One year later she developed severe constitutional symptoms, sicca symptoms, lymphadenopathy, anemia, and interstitial lung disease. Serologies and minor salivary gland were consistent with the diagnosis of SS. This case further supports the association of lymphocytic mastitis with autoimmune diseases and demonstrates that it can even precede the clinical diagnosis of these entities.